ANALYSIS OF THE PHYSICAL HOME ENVIRONMENT AND COMMUNITY BEHAVIOR TOWARDS INCIDENCE OF DENGUE HEMORRHAGIC FEVER IN RIAU PROVINCE (Jurnal Mitra Kesehatan, 2021)
Introduction: Dengue Hemorrhagic Fever (DHF) is still a health problem in Meranti Islands Regency. There has been an increase of 15-25% of cases every year since 2017-2019. The purpose of this study is to determine the correlation between the physical home environment and community behavior towards DHF incidence which include: ventilation, air temperature, water reservoirs, knowledge, and attitudes. Method: It was observational analytic with a cross-sectional design. This research was conducted for three months (February-April 2020). The research subject was 92 samples were selected by the purposive sampling technique. The research instrument was a structured questionnaire and observation sheet. Data analysis using Chi-square test. Results: There were 49 (53.3%) cases of DHF with the physical home environment that was not following the health standards, namely: ventilation (bad=70.7%), air temperature (bad=77.2%), water reservoirs (bad=59.8%), knowledge (low=55,4%), and attitude (negative=55.4%). There was a significant correlation between ventilation (p=0,002), air temperature (p=0,020), water reservoirs (p=0,027), knowledge (p=0,008), and attitudes (p=0,000) toward incidence of DHF (p-value <0.05). Conclusion: The physical home environment and community behavior are related to DHF incidence. Good coordination between health promotion team, local government in providing health education, socialization of healthy homes by empowering local communities.